2022
DOI: 10.3390/curroncol29050235
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Postoperative Complications of Sentinel Node Identification Using the SentiMag® Method and the Use of a Radiotracer in Patients with Breast Cancer

Abstract: (1) Background: The purpose of the study was a retrospective, comparative assessment of complications of the surgical sentinel node biopsy (SNB) procedure in breast cancer using the radiotracer method and the SentiMag® method on groups of patients after 3.5 years of use. (2) Methods: The material was a group of 345 patients with primary surgical breast cancer who underwent the SNB procedure with the use of a radiotracer in combination with wide local excision (WLE), simple amputation (SA) with SNB and an indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…No severe allergic reactions were reported in any of the currently published trials; this can partly be explained by the exclusion of patients with hypersensitivity to iron or dextran compounds and those with pacemakers or metal implants. Dermopigmentation is the most frequently reported complication, with a rate of up to 20% in the injection site, similar to what is found after the injection of blue dye [ 23 , 28 , 48 , 49 ]. Skin staining after SPIO injection is a concern as well, even though several reports showed that most patients did not consider it an upsetting problem [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 53%
“…No severe allergic reactions were reported in any of the currently published trials; this can partly be explained by the exclusion of patients with hypersensitivity to iron or dextran compounds and those with pacemakers or metal implants. Dermopigmentation is the most frequently reported complication, with a rate of up to 20% in the injection site, similar to what is found after the injection of blue dye [ 23 , 28 , 48 , 49 ]. Skin staining after SPIO injection is a concern as well, even though several reports showed that most patients did not consider it an upsetting problem [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 53%
“…This method does not imply a loss of information since the scintigraphic examination can be replaced by one using the magnetic detector; in this way, there would be a complete elimination of the exposure to ionizing radiation both to the healthcare team and the patient [ 18 ]. This will also reduce the time required for the patient’s diagnostic procedure, thus decreasing their psychological stress, which is already of considerable importance, since they are faced with a malignant pathology [ 19 ] ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some issues related to this context (i.e., high costs, few centers with nuclear medicine facilities, potential allergic reactions to the tracer, etc.) have required new tracers to be studied, such as indocyanine green (ICG), superparamagnetic iron oxide (SPIO), and carbon nanoparticles (CNPs) [79][80][81][82].…”
Section: State Of the Art Of Sln Mapping Techniques In Patients Subje...mentioning
confidence: 99%